Demonstration of a modular electrostatic precipitator to control particulate emissions from a small municipal waste incinerator - Panich Intra (2018)
Incineration is conceptually sound as a waste treatment technology. There is, however, concern over its emissions when it is improperly designed and operated. An electrostatic precipitator is one of the most commonly used devices to control particulate emissions from boilers, incinerators and some other industrial processes. In this work, a modular electrostatic precipitator with sizing of 1 m × 1 m×1 m was developed for removal of particulate matter from the exhaust gases of a small waste incinerator. Its design was based on a simple wire-and-plate concept. The corona discharge wires were connected to a positive high-voltage pulse generator, while the collection plates were grounded. The high-voltage pulse generator was used to produce the corona discharge field between the individual discharge wire and the collection plate. The particulate-laden exhaust gas flow was directed across the corona discharge field. The charged particles were deflected outward and collected on the plate. The collection efficiency was evaluated as a mass loading ratio between the difference at the inlet and the outlet to the particulate loading at the inlet of the precipitator. The collection efficiency of this modular electrostatic precipitator design was approximately 80%.